A comprehensive lot-to-lot variation assessment and comparative analysis of the Concerro CE-SDS kit against the Sciex CE-SDS kit for monoclonal antibody size variant analysis - Bhavsar, Ravindra; Patel, Nikita; Jaiswal, Rani; Agrahari, Shailesh; Thanawala, Husain; Patil, Arati (International Journal of Research in Medical Sciences, 2026)
Background: Monoclonal antibodies (mAbs) are complex biotherapeutics whose quality and integrity must be stringently monitored throughout development and manufacturing. Capillary electrophoresis sodium dodecyl sulfate (CE-SDS) is the definitive analytical technique used globally for assessing size heterogeneity, including the presence of low molecular weight (LMW) fragments, high molecular weight (HMW) species, and ensuring accurate estimation of size of protein’s component. The objective of this study was to evaluate the analytical performance and manufacturing consistency of the newly introduced Concerro CE-SDS Kit against the established market innovator, the Sciex CE-SDS kit. Methods: This study performed a head-to-head comparison utilizing the therapeutic monoclonal antibody Ipilimumab (Yervoi®). Analysis was conducted under both reduced and non-reduced conditions. Critical analytical performance indicators, including migration time, calculated peak area (mAu), calculated peak area percent (CPA%) were monitored during this study. Results: The Concerro CE-SDS kit demonstrated analytical performance comparable to the Sciex CE-SDS kit, with similar precision and profile matching. Lot-to-lot variability for the Concerro CE-SDS kit showed %RSD values upto 10%. Conclusions: The Concerro CE-SDS kit is affirmed as a robust, analytically equivalent alternative for high-precision size variant characterization in GxP/QC environments.